2001
DOI: 10.1128/jvi.75.3.1274-1283.2001
|View full text |Cite
|
Sign up to set email alerts
|

Sorting of Marburg Virus Surface Protein and Virus Release Take Place at Opposite Surfaces of Infected Polarized Epithelial Cells

Abstract: Marburg virus, a filovirus, causes severe hemorrhagic fever with hitherto poorly understood molecular pathogenesis. We have investigated here the vectorial transport of the surface protein GP of Marburg virus in polarized epithelial cells. To this end, we established an MDCKII cell line that was able to express GP permanently (MDCK-GP). The functional integrity of GP expressed in these cells was analyzed using vesicular stomatitis virus pseudotypes. Further experiments revealed that GP is transported in MDCK-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 54 publications
4
39
0
Order By: Relevance
“…It has been published earlier that MARV GP is released into the supernatant of GP-expressing cells (43). A recent study by Swenson et al confirmed this observation and, in addition, showed that the amount of GP released from the cells was increased by coexpression of the viral matrix protein VP40 (47).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…It has been published earlier that MARV GP is released into the supernatant of GP-expressing cells (43). A recent study by Swenson et al confirmed this observation and, in addition, showed that the amount of GP released from the cells was increased by coexpression of the viral matrix protein VP40 (47).…”
Section: Resultssupporting
confidence: 69%
“…In MARV-infected polarized MDCK cells, the majority of GP was also transported to the apical membrane; however, the release of infectious progeny virions took place exclusively at the basolateral membrane of the cells. Thus, in the presence of other viral proteins, GP obviously is redirected to an alternative route (43). Another observation indicating a different route of GP transport in the context of the viral infection is intracellular budding of MARV in human macrophages (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the localization of G and F proteins in infected polarized MDCK cells was found to be bipolar, with most of the glycoproteins concentrating at the apical membrane (27). As it is known for several viruses that the glycoprotein distribution does not necessarily determine the site of virus budding (28)(29)(30)(31), the impact of the NiV glycoprotein distribution is not yet known. The aim of this study was thus to elucidate the virus entry and exit pathways in polarized epithelial cells and to clarify the role of vectorial sorting of the NiV envelope proteins in virus spread and release from epithelial cells.…”
mentioning
confidence: 97%
“…Thus, transient polarization of lymphocytes, similar to the permanent polarized nature of epithelia or neurons, is not only central to their physiological function, but also influences virus replication. Selective transport of viral surface and matrix proteins to a specific domain can critically determine cell-to-cell spread and targeted virus release from polarized cells (Danis et al, 2004;Deschambeault et al, 1999;Fuller et al, 1984;Lodge et al, 1997;Mora et al, 2002;Sanger et al, 2001;Tashiro et al, 1990;Zimmer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%